Local Tandem Repeat Expansion in Xist RNA as a Model for the Functionalisation of ncRNA - Brockdorff, Neil (Noncoding RNA, 2018)
Xist, the master regulator of the X chromosome inactivation in mammals, is a 17 kb lncRNA that acts in cis to silence the majority of genes along the chromosome from which it is transcribed. The two key processes required for Xist RNA function, localisation in cis and recruitment of silencing factors, are genetically separable, at least in part. Recent studies have identified Xist RNA sequences and associated RNA-binding proteins (RBPs) that are important for these processes. Notably, several of the key Xist RNA elements correspond to local tandem repeats. In this review, I use examples to illustrate different modes whereby tandem repeat amplification has been exploited to allow orthodox RBPs to confer new functions for Xist-mediated chromosome inactivation. I further discuss the potential generality of tandem repeat expansion in the evolution of functional long non-coding RNAs (lncRNAs).